Recent Advancements of Fungal Xylanase Upstream Production and Downstream Processing - J, Jonathan; Tania, Veren; Tanjaya, Jessica C.; K, Katherine (Indonesian Journal of Life Sciences, 2021)
Xylanase is a hydrolytic enzyme produced by fungi and bacteria utilized in various industrial applications such as food, biobleaching, animal feed, and pharmaceuticals. Due to its wide variety of applications, xylanase's large-scale industrial production has gained researchers' interest. Many factors and methods affect fungal xylanase's production in both upstream and downstream processing stages. The upstream production methods used are submerged fermentation (SmF) and solid-state fermentation (SSF), where SmF involves the usage of liquid substrates, while the SSF applies solid substrates to inoculate the microbes. The downstream processing of fungal xylanase includes extraction, purification, and formulation. The extraction methods used to extract fungal xylanase are filtration and solvent extraction. Meanwhile, the purification methods include ultrafiltration, precipitation, chromatography, Aqueous Two-Phase System (ATPS), and Aqueous Two-Phase Affinity Partitioning (ATPAP). The formulation of xylanase product is obtained in either liquid from the extraction-purification results, which can be converted to powder form using technologies such as spray drying to increase storage life. Moreover, immobilization of xylanase with nanoparticles of SiO2 could produce reusable xylanase enzymes. Several future studies have also been suggested. This review aims to explain the upstream and downstream processes of fungal xylanase production as well as the factors that affect those processes.